The history of Don Quixote de la Mancha - Cervantes Saavedra, Miguel de, 1547-1616.; Boschère, Jean de, 1878-1953.; Shelton, Thomas, fl. 1612. (New York : Hart Pub. Co., 1976)
An abridged version of the adventures of an idealistic country gentleman and his shrewd squire who set out, like knights of old, to search for adventure and right wrongs.
Mode of access: Internet.
Keywords: Knights and knighthood -- Fiction; Spain -- Fiction